2021
DOI: 10.1162/jocn_a_01710
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure of Attentional Control in the Dorsal Attention Network

Abstract: The top–down control of attention involves command signals arising chiefly in the dorsal attention network (DAN) in frontal and parietal cortex and propagating to sensory cortex to enable the selective processing of incoming stimuli based on their behavioral relevance. Consistent with this view, the DAN is active during preparatory (anticipatory) attention for relevant events and objects, which, in vision, may be defined by different stimulus attributes including their spatial location, color, motion, or form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 100 publications
(167 reference statements)
2
18
0
Order By: Relevance
“…Individually, the peak activation for each subject was found to be within the IFJ ROI so defined for 19 of 20 subjects; and for the remaining subject, the peak activation was found to be within two voxels of the IFJ ROI. The DAN ROI was defined in a similar fashion (Rajan et al, 2021). The V4 ROI was defined by the overlap between feature cue-evoked activations (p , 0.05 FDR) and the retinotopically defined hv4 in the probabilistic maps of L. Wang et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individually, the peak activation for each subject was found to be within the IFJ ROI so defined for 19 of 20 subjects; and for the remaining subject, the peak activation was found to be within two voxels of the IFJ ROI. The DAN ROI was defined in a similar fashion (Rajan et al, 2021). The V4 ROI was defined by the overlap between feature cue-evoked activations (p , 0.05 FDR) and the retinotopically defined hv4 in the probabilistic maps of L. Wang et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…The participants reported no prior history of neuropsychological disorders and provided written informed consent. The data from this experiment have been used to investigate different questions in our previously published work (Rajan et al, 2019(Rajan et al, , 2021. Because the analyses conducted here followed this prior work, and effect sizes were taken to be similar to those significant prior findings, no new power analysis was performed before the experiment.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that most tasks require regions that belong to the SAL and DAN networks, it is not clear what would be the performance in a visually oriented task. It is known that the DAN is activated by visual-spatial attention tasks 38 , connected to the ventral attention network 39 and related to visual attention modulated from the ocular dominance 40 . Also, it has been shown that DAN FC changes after acute stress exposure 41 and in sleep problems 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The participants reported no prior history of mental disorders and had normal or correct-to-normal vision. The data from this experiment has been used in previous publications to investigate different questions (Rajan et al, 2019; Rajan et al, 2021; Meyyappan et al, 2021).…”
Section: Methodsmentioning
confidence: 99%